Neonatal sepsis due to Salmonella Typhi and Paratyphi A - Srujana Mohanty; Rajni Gaind; Rachna Sehgal; Harish Chellani; Monorama Deb (Journal of Infection in Developing Countries)
Sepsis due to Salmonella enterica serovar Typhi and Paratyphi A is rare in neonates. Though described as a mild and unrecognized illness in infants, life-threatening complications and even deaths have been reported. We present five cases of neonatal septicaemia due to S. Typhi and S. Paratyphi A. The cases were presented because of their interesting clinical presentations and possible modes of transmission. Salmonella infections should be considered in the differential diagnosis of sepsis neonatorum, especially in endemic areas.